Class II alpha-mannosidase from aspergillus fischeri: energetics of catalysis and inhibition - Shashidhara, K. S.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2009)
Energetics of the catalysis of Class II alpha-mannosidase (E.C.3.2.1.24) from Aspergillus fischeri was studied. The enzyme showed K(cat)/K(m) for Man (alpha 1-3) Man, Man (alpha 1-2) Man and Man (alpha 1-6) Man as 7488, 5376 and 3690 M(-1) min(-1), respectively. The activation energy, Ea was 15.14, 47.43 and 71.21 kJ/mol for a1-3, alpha 1-2 and alpha 1-6 linked mannobioses, respectively, reflecting the energy barrier in the hydrolysis of latter two substrates. The enzyme showed K(cat)/K(m) as 3.56 x 10(5) and 4.61 x 10(5) M(-1) min(-1) and E(a) as 38.7 and 8.92 kJ/mol, towards pNP alpha Man and 4-MeUmb alpha Man, respectively. Binding of Swainsonine to the enzyme is stronger than that of 1-deoxymannojirimycin. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Mannosidase; Energy of activation; kinetics; Swainsonine